In vivo Analysis of CRISPR/Cas9 Induced Atlastin Pathological Mutations in Drosophila - Montagna, Aldo; Vajente, Nicola; Pendin, Diana; Daga, Andrea (Frontiers in Neuroscience, 2020)
The endoplasmic reticulum (ER) is a highly dynamic network whose shape is thought to be actively regulated by membrane resident proteins. Mutation of several such morphology regulators cause the neurological disorder Hereditary Spastic Paraplegia (HSP), suggesting a critical role of ER shape maintenance in neuronal activity and function. Human Atlastin-1 mutations are responsible for SPG3A, the earliest onset and one of the more severe forms of dominant HSP. Atlastin has been initially identified in Drosophila as the GTPase responsible for the homotypic fusion of ER membrane. The majority of SPG3A-linked Atlastin-1 mutations map to the GTPase domain, potentially interfering with atlastin GTPase activity, and to the three-helix-bundle (3HB) domain, a region critical for homo-oligomerization. Here we have examined the in vivo effects of four pathogenetic missense mutations (two mapping to the GTPase domain and two to the 3HB domain) using two complementary approaches: CRISPR/Cas9 editing to introduce such variants in the endogenous atlastin gene and transgenesis to generate lines overexpressing atlastin carrying the same pathogenic variants. We found that all pathological mutations examined reduce atlastin activity in vivo although to different degrees of severity. Moreover, overexpression of the pathogenic variants in a wild type atlastin background does not give rise to the loss of function phenotypes expected for dominant negative mutations. These results indicate that the four pathological mutations investigated act through a loss of function mechanism.